Evolving Science Teacher Professional Development in Asia: A Comparative Mapping of Southeast and East Asian Research - Sylvester T Cortes; Anne S Lorca; Joed E Caballero; Zerry Ayn Z Retubado; Lea B Colita; Ryan G Tubog; Hedeliza A Pineda (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to explore and compare the development trajectories, collaboration structures, and thematic emphases of professional development research for in-service science teachers in Southeast Asia and East Asia, providing insights into how Professional Development (PD) scholarship has evolved across the two regions from 2015 to 2025. Methodology: A comparative bibliometric analysis was conducted using 87 Scopus-indexed publications (2015–2025). Biblioshiny (RStudio) and VOSviewer were used to examine publication trends, authorship networks, institutional and international collaborations, and thematic evolution of professional development research for in-service science teachers in Southeast Asia and East Asia. Main Findings: Results reveal distinct yet complementary orientations. Southeast Asia’s research is largely practice-oriented, reform-driven, and community-based, emphasizing teacher agency, STEM education, and action research. East Asia’s studies are more conceptually grounded, technologically integrated, and methodologically cohesive, reflecting strong engagement with frameworks such as TPACK, argumentation, AI in teaching, and sustained quality assurance in professional development research. Novelty/Originality of this study: This study offers a region-to-region comparative bibliometric mapping of science teacher professional development research in Southeast Asia and East Asia. Through integration of collaboration patterns, thematic evolution, and policy-linked orientations, it advances understanding of regional strengths and proposes a trans-Asian professional development framework that bridges participatory reform with analytical rigor.